Pathobiology of marine and estuarine (CRC Press, 2000)
Pathobiology of Marine and Estuarine Organisms is a comprehensive, up-to-date review of aquatic animal pathobiology covering infectious and non-infectious diseases of vertebrates such as marine mammals and fishes, in addition to diseases of invertebrates such as crustacea, mollusks, and lower phyla. The book provides critical information on viral, fungal, bacterial, parasitic, and neoplastic diseases of fish and invertebrates.